2021
DOI: 10.3390/ijms22136889
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 Interacts with the TREM-1 Receptor Expressed on Monocytes and Thereby Stimulates Generation of Cytotoxic Lymphocytes Active against MHC-Negative Tumor Cells

Abstract: The search for and analysis of new ligands for innate immunity receptors are of special significance for understanding the regulatory mechanisms of immune response. Here we show that the major heat shock protein 70 (Hsp70) can bind to and activate TREM-1, the innate immunity receptor expressed on monocytes. The Hsp70–TREM-1 interaction activates expression of TNFα and IFNγ mRNAs in monocytes and stimulates IL-2 secretion by РВМСs. Moreover, incubation of РВМСs with Hsp70 leads to an appearance of cytotoxic lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Interestingly, granzyme B was found to be incorporated in tumor cells by explicitly binding to mHSP70, which results in perforin-independent apoptosis of the cells [ 44 ]. Moreover, Sharapova and colleagues recently reported another possibility of NK cell activation while investigating a novel exHSP70 target receptor [ 116 ]. They showed that exHSP70 binds TREM-1 on monocytes, leading to the secretion of TNF-α and INF-γ.…”
Section: Role Of Exhsp70: Regulation Of Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, granzyme B was found to be incorporated in tumor cells by explicitly binding to mHSP70, which results in perforin-independent apoptosis of the cells [ 44 ]. Moreover, Sharapova and colleagues recently reported another possibility of NK cell activation while investigating a novel exHSP70 target receptor [ 116 ]. They showed that exHSP70 binds TREM-1 on monocytes, leading to the secretion of TNF-α and INF-γ.…”
Section: Role Of Exhsp70: Regulation Of Immune Responsesmentioning
confidence: 99%
“…The cytokines then stimulate CD4 + T-cells to secrete IL-2, finally activating NK cells. Moreover, CD8 + T-cells are also activated by this mechanism and can kill tumor cells via FasL/Fas interaction [ 116 ]. Interestingly, FasL can trigger the secretion of an HSP70-Tag7 complex in T-cells.…”
Section: Role Of Exhsp70: Regulation Of Immune Responsesmentioning
confidence: 99%
“…Earlier investigated peptides 17.1 and 17.1.A capable of binding specifically to the TNFR1 receptor did not exhibit inhibiting effect (Figure 3). It should be noted that N1 reduced the cytotoxic activity initiated both by the full-length Tag7 and the major heat shock protein Hsp70 which can be also considered as a ligand for TREM-1 [10]. In addition, the peptide binding with sTREM-1 expressed on the cell membrane was investigated.…”
Section: Tag7 Protein N-terminal Peptides Interact With the Receptor Trem-1 And Inhibit The Cytotoxic Activity Of Pbmcsmentioning
confidence: 99%
“…The described ligands of TREM-1 include the high mobility group box 1 protein (HMGBI) nuclear protein and the innate immune protein PGLYRP1 (Tag7) [7][8][9]. Our recent study has demonstrated that Hsp70, the major heat shock protein, can be also considered as another ligand for TREM-1 [10]. In turn, TREM-1 is expressed on monocytes, neutrophils, antigen-presenting cells and NK cells, as well as selective T-and B-lymphocyte populations, epithelial cells and fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, TREM-1 ligands have been investigated as a potential tool to regulate inflammation. Recently, the following ligands of TREM-1 receptor have been identified: HMGBP1, PGLYRP1 and Hsp70 [ 14 , 23 , 24 , 25 ]. Some evidence suggests that Hsp70 is a novel ligand for TREM-1 and has an impact upon its activation [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%